A neurobiological hypothesis for the classification of schizophrenia: type a (hyperdopaminergic) and type B (normodopaminergic). (July 2014) - Howes, Oliver D.; Kapur, Shitij
Summary: Schizophrenia is usually classified based on clinical presentation. However, the conventional paranoid–disorganised–residual distinctions have had limited clinical utility. Here we draw on the evidence for differences in pathophysiology underlying treatment response to propose a subclassification based on neurobiology to guide diagnostic testing and treatment.